2018
DOI: 10.1016/j.radcr.2017.09.025
|View full text |Cite
|
Sign up to set email alerts
|

MRI of acquired Brown syndrome: a report of two cases

Abstract: Brown syndrome is characterized by upward gaze impairment while the eye is in adduction. It is caused by abnormalities involving the superior oblique tendon-trochlea complex. Imaging can help confirm the diagnosis, shed light on its etiology, and determine the best course of treatment. However, reports of magnetic resonance imaging findings of acquired Brown syndrome are scarce in the literature. Here, we describe magnetic resonance imaging features of 2 cases of acquired Brown syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…MRI in our case showed asymmetric thickening of the superior oblique tendon. Lang et al reported a similar MRI finding in 2 cases [ 11 ]. In our case, contrast could have shown better characterization of the superior oblique tendon, similar to that reported by Lang et al [ 11 ].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…MRI in our case showed asymmetric thickening of the superior oblique tendon. Lang et al reported a similar MRI finding in 2 cases [ 11 ]. In our case, contrast could have shown better characterization of the superior oblique tendon, similar to that reported by Lang et al [ 11 ].…”
Section: Discussionmentioning
confidence: 63%
“…Lang et al reported a similar MRI finding in 2 cases [ 11 ]. In our case, contrast could have shown better characterization of the superior oblique tendon, similar to that reported by Lang et al [ 11 ]. Although spontaneous recovery has been previously reported in the literature [ 12 ], less invasive methods may be initially attempted to treat acquired Brown syndrome, such as local steroid injection or anti-inflammatory agents, as in our case [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 63%
“…Lang et al postulates that idiopathic cases of Brown’s Syndrome may be due to subtle abnormalities of the superior oblique’s passage through the trochlea leading to local inflammation. 8 The etiology of Brown’s syndrome in this case was likely inflammatory given his steroid response and subtle MRI findings. Kushner suggested that cryptogenic cases of inflammatory Brown’s syndrome are best treated with injection of steroids into the trochlear area.…”
Section: Discussionmentioning
confidence: 80%
“…The same ring-like enhancement is clearly discernible in the MRI of a patient with bilateral trochleitis in the context of adult-onset Still disease published by Gutmark et al (13). Further studies have previously identified enhancement of the trochlear region in acquired Brown syndrome (12,22–27). Elhusseiny et al used the term trochleitis in their case report of a patient with underlying juvenile idiopathic arthritis and contrast enhancement around the trochlea, where the typical limitation of extraocular movements as seen in Brown syndrome was missing.…”
Section: Discussionmentioning
confidence: 99%